Cyberbullying : bullying in the digital age - Kowalski, Robin M. (Wiley-Blackwell, 2012)
"Psychologists explore the reality of cyberbullies. Millions of children are affected by bullies each year. Advances in social media, email, instant messaging, and cell phones, however, have moved bullying from a schoolyard fear to a constant threat. The second edition of Cyberbullying offers the most current information on this constantly-evolving issue and outlines the unique concerns and challenges it raises for children, parents, and educators. Authored by psychologists who are internationally recognized as experts in this field, the text uses the latest research in this area to provide an updated, reliable text ideal for parents and educators concerned about the cyberbullying phenomenon"--